TRANSFORMASI KEBUDAYAAN WAYANG KULIT SUKU JAWA: DARI TRADISI KLASIK KE ERA MODERN DI KABUPATEN OGAN KOMERING ULU - Vrischa Oktaviyana; Herni Ramayanti; Marshanda Lievia; Avira Miranda; Anadia Maudy (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Wayang kulit is one of Indonesia's intangible cultural heritages that holds high historical, philosophical, religious, and educational values. However, the development of information technology, cultural globalization, and changes in people's entertainment consumption patterns have caused a transformation in the existence and function of wayang kulit, especially among the Javanese community living in Ogan Komering Ulu (OKU) Regency. This study aims to analyze the forms of cultural transformation of wayang kulit from classical tradition to the modern era and identify the factors influencing these changes. The research uses a descriptive qualitative approach with a literature study method supported by social observation of the development of wayang kulit arts in Ogan Komering Ulu Regency. The analysis is carried out through cultural transformation theory, which emphasizes changes in form, function, values, and adaptation to technological developments. The results of the study show that The transformation of wayang kulit occurs in five main aspects, namely changes in the form and appearance of performances, shifts in socio-cultural functions, adaptation to digital technology, changes in community behavior patterns, and a process of gradual and continuous change. Digitalization has become a dominant factor that allows wayang kulit to survive amid modern popular culture competition. However, this transformation also has the potential to reduce public understanding of the philosophical values contained in wayang if not balanced with systematic preservation efforts. This study concludes that cultural transformation is not a threat to the existence of wayang kulit, but rather a form of adaptation to keep the culture relevant to the needs of modern society.